Analisis Kurva Intensity Duration Frequency (IDF) pada Daerah Aliran Sungai (DAS) Yeh Sumbul - Astiti, Sagung Putri Chandra; Arsana, I Gusti Ngurah Kerta (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
AbstractThe Yeh Sumbul River Basin (DAS) is a river basin that crosses Jembrana Regency and Buleleng Regency, where the watershed area in Jembrana Regency is 71.34 km2 and the watershed area in Buleleng Regency is 39.31 km2. The Yeh Sumbul Watershed has a total watershed area of 110.65 km2, has a river length of 27.4 km with a pharennial river type. Based on the large potential of the Yeh Sumbul Watershed, researchers analyzed the Intensity-Duration-Frequency (IDF) curve to determine the planned flood discharge in the analyzed area. The results of the calculation of the standard deviation of rainfall in the data are 21.89. The value of the rainfall variation coefficient is 0.247, the value of the rainfall skewness coefficient is 0.457 and the value of the rainfall skewness coefficient is 3.614. The average y value of the rainfall log is 1.94, the standard deviation value is 0.108 and the skewness coefficient value is -0.0584. In the pattern of the IDF curve depiction that has been analyzed, it is found that the greater the duration, the lower the intensity and the greater the recurrence period, the greater the intensity of the rain that occurs